2012
DOI: 10.1056/nejmoa1208594
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Diagnosis by Whole-Genome Sequencing of a Prenatal Sample

Abstract: SUMMARY Conventional cytogenetic testing offers low-resolution detection of balanced karyotypic abnormalities but cannot provide the precise, gene-level knowledge required to predict outcomes. The use of high-resolution whole-genome deep sequencing is currently impractical for the purpose of routine clinical care. We show here that whole-genome “jumping libraries” can offer an immediately applicable, nucleotide-level complement to conventional genetic diagnostics within a time frame that allows for clinical ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
174
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 180 publications
(176 citation statements)
references
References 17 publications
2
174
0
Order By: Relevance
“…For other regions, alignment to the reference sequence cannot be resolved. These include breakpoints of balanced translocations and inversions, which can evade detection, unless paired-end sequencing is performed, wherein both sides of a fragment are linked together and sequenced in a way that the sequence is part of a single read (Talkowski et al 2012). It has been estimated that at least one exon of up to 3000 genes has a highly homologous pseudoexon and some genes have entire pseudogenes (Xue et al 2014).…”
Section: Coverage Of Coding Exons and Mutations That Are Not Well Detmentioning
confidence: 99%
See 1 more Smart Citation
“…For other regions, alignment to the reference sequence cannot be resolved. These include breakpoints of balanced translocations and inversions, which can evade detection, unless paired-end sequencing is performed, wherein both sides of a fragment are linked together and sequenced in a way that the sequence is part of a single read (Talkowski et al 2012). It has been estimated that at least one exon of up to 3000 genes has a highly homologous pseudoexon and some genes have entire pseudogenes (Xue et al 2014).…”
Section: Coverage Of Coding Exons and Mutations That Are Not Well Detmentioning
confidence: 99%
“…Genomic sequencing was performed, which revealed disruption of CHD7, the gene involved in CHARGE syndrome. This diagnosis was achieved in 13 d by paired-end sequencing of large-insert (2-kb) fragments of a whole-genome "jumping library" (Talkowski et al 2012). Filges et al also sequenced the exomes of a trio (affected fetus and both parents) for a family with one healthy child and two affected fetuses with recurrent intrauterine growth restriction, brain abnormalities (including microcephaly), renal and genitourinary abnormalities.…”
Section: Exome Sequencingmentioning
confidence: 99%
“…There were 118 studies obtained from the key word search. After screening titles and abstracts, 8 studies related to microarray prenatal diagnosis were obtained and selected for further screening by reading the full text (Lim et al, 2010;Chiu et al, 2010;Papoulidis et al, 2012;Stumm et al, 2012;Talkowski et al, 2012;Schmid et al, 2013;Simpson, 2013;Vaiopoulos et al, 2013). Among these, 2 studies were disease case reports and 5 investigated microarray techniques for different fields but did not judge noninvasive prenatal accuracy at a large scale; therefore, these studies were excluded.…”
Section: Literature Selectionmentioning
confidence: 99%
“…WGS technologies were used to complement standard cytogenetic analyses on an amniotic fluid sample in order to specifically discover disruption of the CHD7 gene, which causes CHARGE syndrome [16]. Although this prenatal diagnosis relied on amniocentesis, an invasive procedure with inherent risks, it has now been shown that WGS of a human fetus may soon be clinically feasible using noninvasive techniques.…”
Section: Discovery and Diagnosis-the Translation Of Wes/ Wgs Into Thementioning
confidence: 99%